DIAGNOSA KETERAMPILAN MENGAJAR GURU PAI PADA MATERI YANG DIANGGAP TABU DI SDIT AL-FIRDAUS BANJARMASIN - Abdullah Husein; Nuryadin Nuryadin (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2021)
Fiqh material requires a special skill for an educator in delivering it, let alone intersect with the problem of delivering material that considered taboo by both educators and students. Like delivering material about the purification of the big hadas (Mandi Junub), also conveyed the material of the request prayer, and fasting (Haid, Nifas Jimak). The skills of a teacher are needed in order to convey taboo material in Fiqh to level students elementary school in proportion. This article aims to analyze the skills of an educator in delivering Fiqh material which is taboo provide understanding to elementary school students. This article will studied using descriptive qualitative research methods by going directly to the field searches for data and narrates the data with a theory that concerned. The results of this study educators need special skills in teaching in order to be able to convey Fiqh material that is considered taboo to level students elementary school properly and in proportion. Conclusions from this research skills delivering Fiqh material from educators can provide understanding to participants educate on Fiqh material which is considered taboo